2016
DOI: 10.3389/fphys.2016.00205
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Rostral Ventrolateral Medulla (RVLM) Bombesin Receptor Type 1 Decreases Blood Pressure and Sympathetic Activity in Anesthetized Spontaneously Hypertensive Rats

Abstract: Intrathecal injection of bombesin (BBS) promoted hypertensive and sympathoexcitatory effects in normotensive (NT) rats. However, the involvement of rostral ventrolateral medulla (RVLM) in these responses is still unclear. In the present study, we investigated: (1) the effects of BBS injected bilaterally into RVLM on cardiorespiratory and sympathetic activity in NT and spontaneously hypertensive rats (SHR); (2) the contribution of RVLM BBS type 1 receptors (BB1) to the maintenance of hypertension in SHR. Uretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…; Pinto et al . ). AITC evoked relatively similar bradypnoeic breathing responses in conscious WKY and SH rats, regardless of the route of administration.…”
Section: Discussionmentioning
confidence: 97%
“…; Pinto et al . ). AITC evoked relatively similar bradypnoeic breathing responses in conscious WKY and SH rats, regardless of the route of administration.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the RVLM plays a key role in regulation of sympathetic out flow [ 24 , 25 ]. The abnormalities of the RVLM in the regulation of sympathetic nerve activity contribute to cardiovascular dysfunction like chronic heart failure and hypertension [ 25 , 26 ]. Previous studies have suggested that HCY plays a role as a neurotransmitter or neuromodulator in the medullary autonomic nuclei [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Localization of the neurons involved suggests possible different regions of bombesin-like peptide action. Bombesin administered directly into RVLM induces increases in MAP both in normotensive and spontaneously hypertensive rats (SHR), and BIM-23127 reduces MAP and renal sympathetic nerve activity in SHR but not in normal rats [25]. On the other hand, the studies by Lateef et al [26] show an increase in sympathetic nervous system activity, with subsequent pressor and tachycardic effects, after the activation of hypothalamic BB 3 receptors.…”
Section: Discussionmentioning
confidence: 99%